2018
DOI: 10.1093/jac/dkx532
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the ST101 clone on fatality among patients with colistin-resistant Klebsiella pneumoniae infection

Abstract: Besides ICU stay, ST101 was found to be a significant independent predictor of patient mortality among those infected with ColR-Kp. A significant association was detected between ST101 and OXA-48. ST101 may become a global threat in the dissemination of colistin resistance and the increased morbidity and mortality of K. pneumoniae infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…The predominant ST observed was ST101, an emerging highrisk clone detected worldwide and associated with different carbapenemases and high mortality (Navon-Venezia et al, 2017;Can et al, 2018). In a recent European survey of CRKP isolates, including 244 hospitals in 32 countries, four major clonal lineages accounted for roughly 70% of the carbapenemaseproducing isolates, including ST 11, 15, 101, 258/512 and their derivatives (David et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The predominant ST observed was ST101, an emerging highrisk clone detected worldwide and associated with different carbapenemases and high mortality (Navon-Venezia et al, 2017;Can et al, 2018). In a recent European survey of CRKP isolates, including 244 hospitals in 32 countries, four major clonal lineages accounted for roughly 70% of the carbapenemaseproducing isolates, including ST 11, 15, 101, 258/512 and their derivatives (David et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…were identi ed among the CPE-infected patients, something previously reported in South and Southeast Asia (46,51).…”
Section: Discussionmentioning
confidence: 56%
“…In our study, ColR-HvKP ST101 isolates were found to be associated with VAP infections (p=0.009). In one of our previous studies, 30 day fatality of infections with ST101 K.pneumoniae was found to be 72% (30). The ST395 clone is known as a potentially high-risk clone (32), and recent studies pointed out the emergence of carbapenem-resistant ST395 in France and Italy (33, 34).…”
Section: Discussionmentioning
confidence: 89%
“…K.pneumoniae ST101 is known as hypervirulent clone mostly responsible for pneumonia and bacteremia in intensive care units. (30, 31). In our study, ColR-HvKP ST101 isolates were found to be associated with VAP infections (p=0.009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation